EDITORIAL BY M. TOBINO (Fiep Bulletin - online, 2012)
- John Andrews: MISSION ACCOMPLISHED - FIEPAND ITS HISTORICAL ROLE - LISAHEINILÄ: A LIFE COMMITTED TO PHYSICAL EDUCATION AND TO FIEP - FIEP: PROTAGONIST OF THE WORLD PHYSICAL EDUCATION FOR 80 YEARS - THE FUTURE OF FIEP - FIEPAND OLYMPISM - THE SUCCESS IN MONTERREY - GOOD-BYE, PRESIDENT - FIEP AND THE REAFFIRMATION OF ITS COMMITMENTS - NOW IS THE TIME TO SEEK THE PHYSICAL CULTURE - SCHOOL PHYSICAL EDUCATION CRISIS IN THE WORLD - FIEP, PEACE AND SOLIDARITY - FIEP AND EUROPE - PRINCE FAISAL PRIZE